Gamification and data analytics to reduce smartphone addiction - Lal, Srishti (2017)
“Nomophobia” is the phobia of being out of mobile phone contact. This project is aimed at developing a proof-of-concept for using techniques of gamification and data analytics for addressing nomophobia. With the collection of these techniques, the project aims to motivate users to focus on other productive work as well as real social interactions instead of being glued to their smartphone screens.